2020
DOI: 10.3389/fnins.2020.547069
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Brain and Spinal Stimulation for Pain and Related Symptoms in Multiple Sclerosis: A Systematic Review

Abstract: Background: Neuropathic and nociceptive pain frequently affect patients with multiple sclerosis (MS), with a prevalence close to 90% and significant impact on general health and quality of life. Pharmacological strategies are widely used to treat pain in MS, but their effectiveness and side-effects are controversial. Among non-pharmacological treatments for pain, non-invasive brain and spinal stimulation (NIBSS) has shown promising preliminary results in MS.Objective: Systematic review to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…Although the mechanisms of MS pain are not fully understood, descending pain modulatory system dysfunction has been linked to human chronic pain conditions ( 54 ). And in patients with MS, the processes of brain networks that mediate pain relief may be disrupted in part ( 55 ). Stimulation on M1 is supposed to induce analgesic effects through an antidromic top-down modulation of thalamo-cortical pathways ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of MS pain are not fully understood, descending pain modulatory system dysfunction has been linked to human chronic pain conditions ( 54 ). And in patients with MS, the processes of brain networks that mediate pain relief may be disrupted in part ( 55 ). Stimulation on M1 is supposed to induce analgesic effects through an antidromic top-down modulation of thalamo-cortical pathways ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…And in patients with MS, the processes of brain networks that mediate pain relief may be disrupted in part ( 55 ). Stimulation on M1 is supposed to induce analgesic effects through an antidromic top-down modulation of thalamo-cortical pathways ( 55 ). In addition, previous study found that in healthy volunteers theta-burst stimulation (TBS) seemed more analgesic than high frequency repetitive transcranial magnetic stimulation and a higher number of pulses of prolonged continuous TBS might result in stronger analgesic effects ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the management of chronic pain, the challenge experienced in other pathological conditions associated with neuropathic pain, are also relevant to MS. Both pharmacological and non-pharmacological approaches are used, although further studies are needed to establish the effectiveness of these therapies ( 69 , 266 , 267 ). Importantly, the evaluation of pharmacological therapies in EAE or other models of MS, need to be performed in a manner that can be applicable in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…While effective for many patients, invasive procedures introduce potential for complications as well as waning pain relief with time [ 60 , 61 , 62 ]. Many patients consider alternative interventional therapies either in lieu of or in combination with current standard options [ 63 , 64 , 65 ]. We therefore expand upon these options and their supporting evidence in the treatment of CNP below.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Such modalities include repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), transcranial random noise stimulation (tRNS) and cranial electrotherapy stimulation (CES) [ 63 , 66 ]. These methods have been applied to a range of CNP syndromes including CPSP, post-SCI pain, and MS [ 65 , 67 , 68 ], although the efficacy of these therapies remains under investigation in the management of neuropathic pain.…”
Section: Alternative Therapiesmentioning
confidence: 99%